Effective Use of Sacrificial Zinc Anode as a Suitable Repair Method for Severely Damaged RC Members Due to Chloride Attack - Pinta Astuti; Rahmita Sari Rafdinal; Daisuke Yamamoto; Volana Andriamisaharimanana; Hidenori Hamada (Salehan Institute of Higher Education, 2022)
In many cases, the repair strategy by using sacrificial anodes for cathodic protection in real RC structures requires additional zinc anodes after several years due to the decreasing protective area. This experimental study evaluates the effectiveness of time lag application of sacrificial anode cathodic protection applied to RC beam specimens that deteriorated severely due to chloride attack. In the experiment, sacrificial anodes and cathodic protection (SACP) were applied to 41-year-old RC beam specimens exposed to natural marine environments in which the embedded steel bars were significantly corroded. The repair work was performed in three stages. Instant-off and rest potential tests of steel bars were conducted periodically to demonstrate the time-dependent depolarization value. In the first stage, a polymer-modified mortar as a patch repair material was cast to replace the concrete in the middle tensile part with small sacrificial anodes embedded in the mortar. After the protective current reaches an equilibrium state, the sacrificial anodes are disconnected from the steel bars for a year, defined as the second stage. During the one year in the second stage, the steel bar in the patch repair area remained passive, without any sign of corrosion. As for the third stage, additional sacrificial anodes were installed in the existing concrete part to protect the steel in it. From one year of observation after applying sacrificial anodes to old concrete parts, the time lag SACP application of both in patch and non-patch repair parts was clarified to be effective in stopping the corrosion of steel bar in both parts until 20–30 years based on the service life prediction. Doi: 10.28991/CEJ-2022-08-07-015 Full Text: PDF